Pengaruh Pendekatan Pembelajaran Problem Posing terhadap Kemampuan Berpikir Kritis Matematis Siswa - Alani, Nabella (Jurnal Penelitian Pendidikan, 2024)
This study aims to analyze and describe the effect of implementing learning using a problem posing approach on students' acquisition of critical mathematical thinking skills. The method in this study is quantitative with a Quasi Experiment type. In this study, it was concluded that (i) the problem posing approach had an effect on students' mathematical critical thinking abilities, (ii) this approach was also proven to be able to improve students' mathematical critical thinking abilities, this was obtained based on the N-gain test which had been carried out where the N-gain score was obtained for the problem posing approach is 0.67 which is included in the medium category. So, based on the research results, it can be concluded that the problem posing learning approach has an effect on students' mathematical critical thinking abilities, apart from that this learning approach can also improve students' mathematical critical thinking abilities.